A híbrida Barquinha: uma revisão da história, das principais influências religiosas e dos rituais fundamentais - Santos, Ricardo Assarice dos (2017)
Created in 1945 in Rio Branco (AC) by Daniel Pereira de Mattos (1888-1958), the Barquinha is a highly complex and little studied religious movement that is influenced by black, white and amerindian religious matrices. Through the drinking of the Daime (ayahuasca), rituals of mediumistic trance, intense Christian devotion, altruistic ideals, and an ample marine and esoteric imagery, this ayahuasca line flourished in several ramifications after the death of its founder and, although discreet, has been gaining adherents of diverse brazilian localities and social contexts. The main objective of this work was to identify and present the history; the main religious influences and the fundamental rituals of the Barquinha line. In addition, the dissertation sought to point out and expand the main concepts used by the researchers of this religious movement, in order to foster some reflections previously presented by them. For this, a systematic bibliographical survey was carried out on the Barquinha literature, which contents had been analyzed and organized in four chapters, in the light of the concepts like symbolic anthropology, from Clifford Geertz, and cultural hybridism, from Peter Burke. In addition to updating the literature on the timeline of this religious movement and identifying its main rituals and religious influences, it was possible to recognize that most of the authors who study Barquinha use the concepts of syncretism and eclecticism to define this religious movement. It was possible to note that most of the authors emphasize the use of ayahuasca in their reviews, not reliably highlighting the influence of esotericism on the symbolic constitution of this religious movement. Finally, through the concept of cultural hybridization, it was possible to broaden the understanding of the constituent processes of this religious movement